Substantiation of the Process of Developing a Scorecard for a Comprehensive Evaluation of Hop Growing - Nadezhda DANILOVA; Evgenii IVANOV; Liia MALININA; Sergei KHRISTOLIUBOV; Mariia TOLSTOVA (Communications of International Proceedings, 2021)
The information background of economic analysis includes not only the sources of information themselves, but also a system of economic indicators characterizing the operational and financial activities of a company. The list of economic indicators as a whole is very extensive, therefore, the management of the enterprise has an objective of identifying the most important of them for operational and current control, for forecasting. The main criterion for such a choice is the goals and objectives of development. However, we always have to take into account the performance features of a particular company, including its structure, type of activity, etc. This is especially true for organizations of the agro-industrial complex, where a special place is occupied by external factors, such as weather conditions. The most promising area of the comprehensive analysis of commercial organization activities is the development of key performance indicators.
Keywords: Comprehensive Efficiency Analysis; Key Performance Indicators; Crop Production; Hop Production.